GE_GERICHTE C/25507/2015 vom 14. Juni 2019 - GE Cour de justice (2019)
CONTRAT D'ENTREPRISE;PRIX DE L'OUVRAGE;DÉFAUT DE LA CHOSE;AVIS DES DÉFAUTS;DROIT DE RÉTENTION;DÉPENS | CO.373.al1; CO.367.al1; CO.368; CO.41.al1; CC.895.al1